Pengaruh pemberian jenis pakan yang berbeda terhadap pertumbuhan dan kelangsungan hidup benih ikan Gabus (Channa striata) - Sri Herlina (Fakultas Peternakan Universitas Kristen Palangka Raya, 2016)
This study aims to determine the growth and survival of snakehead fish (Channa striata) seeds fed with different types of feeds. The experimental design used completely randomized design (CRD) with 3 treatments and 5 replicates that were fed with earthworms, snails, and pellets. The results showed that the different types of feeds very significant effect on the growth of snakehead fish seed. Absolute weight growth of earthworms treatment, snails treatment and pellets treatment were 0.26 g, 0.12 g and 0.08 g respectively. The survival of snakehead fish seeds during the study were 100% in all treatments. Water quality during the research was still in range for growth and survival of snakehead fish seeds. Key words : Channa striata, earthworms, snails, pellets, growth.